2020
DOI: 10.1111/jgh.15314
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of the learning curve to achieve satisfactory adenoma detection rate

Abstract: Background and Aim The number of colonoscopies required to reach satisfactory adenoma detection rate (ADR) is not well established. The aim of this study was to identify the appropriate number of procedures required to attain satisfactory ADR for those well‐trained endoscopists who have a cecal intubation rate (CIR) ≥ 90% and start to perform colonoscopy independently. Methods All endoscopists with compelete independent colonoscopy data during career in our database were enrolled. The number of procedures requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, when the analysis was restricted to studies only including experienced endoscopists, LCI did not show superiority over WLI. It has been reported that the experience of endoscopists was significantly associated with adenoma detection when using WLI, 35 which means that experts could perform well even when they use WLI but trainees could not. Considering that AAs, SSL, and FLs are difficult to detect during colonoscopy, it is reasonable that there is no significant difference between LCI and WLI for experts.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the analysis was restricted to studies only including experienced endoscopists, LCI did not show superiority over WLI. It has been reported that the experience of endoscopists was significantly associated with adenoma detection when using WLI, 35 which means that experts could perform well even when they use WLI but trainees could not. Considering that AAs, SSL, and FLs are difficult to detect during colonoscopy, it is reasonable that there is no significant difference between LCI and WLI for experts.…”
Section: Discussionmentioning
confidence: 99%